O engajamento político-cultural de Nietzsche em suas reflexões sobre a arte - Barcelos, Edimar (2018)
The present research aims to address how Nietzsche was an extremely engaged thinker with the cultural issues of his time in his reflections on art. Taking as a background the idea of a Nietzsche who through philosophy and art criticizes culture, we will defend a concept of engagement, what anchored Nietzsche's reflections on art. Nevertheless, this indicates that his views were not only a purely aesthetic concern, but a cultural political. This hypothesis of cultural political engagement will be demonstrated through the concepts of Bildung and popular music in the writings of the so called first Nietzsche. Finally, our work takes into consideration the text "The Wagner Case". In this regard, we will be analysed politically culturally as a critique of the modernity project, working concepts such as décadence, nihilism, decadent art, cultural industry and great politics; all this, based on the general idea of a culturally politically engaged of Nietzsche.